1992
DOI: 10.2307/1511316
|View full text |Cite
|
Sign up to set email alerts
|

Transition for Youths with Learning Disabilities: A Focus on Developing Independence

Abstract: Youths with learning disabilities encounter more difficulty in making a successful transition to employment and independence than their nondisabled peers. Consequently, they can benefit from implementation of recent federal legislation and the accompanying requirements for transition planning and services. Of particular value for youths with learning disabilities is the philosophy underlying these legislative initiatives of self-determination for individuals with disabilities. For youths with learning disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The present findings would confirm those of other studies showing that the cognitive characteristics of LD are not necessarily outgrown by adolescence, but may persist into adulthood (Goldstein, 1990;Goldstein et al, 1993;McCue & Goldstein, 1991;Spreen, 1987;Spreen & Haaf, 1986). These results also support the work of Reiff and deFur (1992) and others (Axelrod & Zvi, 1992;Cordoni et al, 1981;Morris & Walter, 1991), who studied college students in particular and found that students with LD continued to experience difficulties in selected academic areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present findings would confirm those of other studies showing that the cognitive characteristics of LD are not necessarily outgrown by adolescence, but may persist into adulthood (Goldstein, 1990;Goldstein et al, 1993;McCue & Goldstein, 1991;Spreen, 1987;Spreen & Haaf, 1986). These results also support the work of Reiff and deFur (1992) and others (Axelrod & Zvi, 1992;Cordoni et al, 1981;Morris & Walter, 1991), who studied college students in particular and found that students with LD continued to experience difficulties in selected academic areas.…”
Section: Discussionsupporting
confidence: 92%
“…The increased accessibility of postsecondary education has resulted in the dramatic rise in the number of students with learning disabilities (LD) who pursue higher education (Reiff & deFur, 1992;Saracoglu, Minden, & Wilchesky, 1989). In fact, Mangrum and Strichart (1988) reported that students with LD are the single fastestgrowing group with disabilities on college campuses today.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All postsecondary LD service providers must continue to assist students with the development of their knowledge and skills, but must be careful not to allow students to become overly dependent on their services. Postsecondary LD program directors and service providers should begin to focus on facilitating the learning process for students with LD so that students can learn how to independently function in a postsecondary environment (Brinckerhoff, McGuire, & Shaw, 1993;Carlson, 1985;Reiff & deFur, 1992;White, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings of this study are important for secondary professionals who assist students with learning disabilities in their transition from high school to colleges or universities. Secondary personnel need to develop an understanding of the types of service delivery practices available to two-and four-year postsecondary students with learning disabilities so that the student can make knowledgeable decisions about postsecondary education (Reiff & deFur, 1992).…”
mentioning
confidence: 99%